2018
DOI: 10.3892/ol.2018.7734
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis for tumor vascular normalization of Endostar on hepatoma 22 tumor-bearing mice is involved in the immune response

Abstract: Tumor vascular normalization involved in immune response is beneficial to the chemotherapy of tumors. Recombinant human endostatin (Endostar), an angiogenesis inhibitor, has been demonstrated to be effective in hepatocellular cancer (HCC). However, its vascular normalization in HCC and the role of the immune response in angiogenesis were unclear. In the present study, effects of Endostar on tumor vascular normalization were evaluated in hepatoma 22 (H22) tumor-bearing mice. Endostar was able to inhibit the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…It was shown to promote the efficiency of chemotherapy during the treatment of advanced non-small cell lung cancer phase II/III clinical trials [ 97 ]. Preclinical studies of Endostar also showed anti-angiogenic effects in HCC in vitro [ 98 ] and in vivo [ 99 ], suggesting that combination therapy with Endostar could be considered for the treatment of HCC.…”
Section: Pericellular Proteoglycan: Collagen Xviii/endostatinmentioning
confidence: 99%
“…It was shown to promote the efficiency of chemotherapy during the treatment of advanced non-small cell lung cancer phase II/III clinical trials [ 97 ]. Preclinical studies of Endostar also showed anti-angiogenic effects in HCC in vitro [ 98 ] and in vivo [ 99 ], suggesting that combination therapy with Endostar could be considered for the treatment of HCC.…”
Section: Pericellular Proteoglycan: Collagen Xviii/endostatinmentioning
confidence: 99%
“…Such normalized tumor blood vessels can transport more chemotherapeutic agents to tumor tissues, make cytotoxic agents more effectively. 3 In order to improve the efficacy of chemotherapy, endostar can be used to improve NACT reactivity, DEC-MRI can be used to monitor NACT reactivity in real time. DCE-MRI was based on T1-weighted images and then injected with contrast agent to obtain a series of images of contrast agent transport, distribution and outflow of tumor tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated interstitial fluid pressure (IFP) in B16F10 tumor keep drugs out of vascular wall probably accounted for that 4143. We further administrated Endostar to promote tumor vessel normalization following procedure addressed before,44,45 expected to normalize the tumor microenvironment (improving vascular integrity, reducing IFP, and so on). The alternation of vasculatures of tumor was presented in Figure 12A and B.…”
Section: Resultsmentioning
confidence: 99%